Um estudo empírico sobre o impacto da confiança no desempenho de projetos distribuídos de desenvolvimento de software - Gomes, Vanessa Marcos (2013)
Trust is often defined as the belief that a person will meet the positive expectations of another. The importance of trust in distributed software development has been recognized by researchers. Although several studies have discussed the subject, little is known about the impact of trust (or lack thereof) in the distributed software development project performance. In this sense, an empirical study was conducted in order to identify factors that influence trust in projects and what are the impacts of these factors on project performance indicators. This research was developed using both secondary (systematic literature review) and primary (field study and survey) research methods. The results indicate that availability, competence, experience, face-to-face communication and leadership are among the factors that positively influence performance metrics in software development projects. As a way of presenting the results of this research, we developed a preliminary theoretical model of the impact of trust in the distributed software development project performance. This model can be used by researchers as a framework to investigate the subject and by professionals to better manage and organize their distributed teams.